2019
DOI: 10.1638/2018-0121
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Staphylococcal Species Cultured From Captive Livingstone's Fruit Bats (Pteropus Livingstonii) and Their Environment

Abstract: The Infectious Diseases Data Observatory (IDDO, https://www.iddo.org) has launched a clinical data platform for the collation, curation, standardisation and reuse of individual participant data (IPD) on treatments for two of the most globally important neglected tropical diseases (NTDs), schistosomiasis (SCH) and soiltransmitted helminthiases (STHs). This initiative aims to harness the power of data-sharing by facilitating collaborative joint analyses of pooled datasets to generate robust evidence on the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Prior to WNS, skin diseases were not commonly reported in bats, although dermatophytes are known to grow on bat skin ( Simpson et al , 2013 ; Lorch et al. , 2015 ; McAlpine et al , 2016 ) and dermatitis has been documented ( Goodnight, 2015 ; Fountain et al , 2017 , 2019 ). A global survey of captive bats found that some species are more frequently reported with skin diseases compared to others, and some skin lesions show seasonal patterns with increased frequency in the winter for bats exposed to outdoor temperatures ( Fountain et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to WNS, skin diseases were not commonly reported in bats, although dermatophytes are known to grow on bat skin ( Simpson et al , 2013 ; Lorch et al. , 2015 ; McAlpine et al , 2016 ) and dermatitis has been documented ( Goodnight, 2015 ; Fountain et al , 2017 , 2019 ). A global survey of captive bats found that some species are more frequently reported with skin diseases compared to others, and some skin lesions show seasonal patterns with increased frequency in the winter for bats exposed to outdoor temperatures ( Fountain et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Presumptive S. aureus isolates were screened for methicillin resistance using oxacillin-resistance screening agar (ORSAB, Oxoid) and those from captive bats were further tested for antimicrobial resistance (AMR) by disc diffusion on Muller-Hinton agar as described in Fountain et al 19 .…”
Section: Methodsmentioning
confidence: 99%
“…There is convincing evidence of multifarious host adaptations in this species, involving large-scale changes in gene content, or more subtle changes in coding sequences 16 , 17 . S. aureus is also an opportunistic pathogen, and is an important cause of skin and soft-tissue infections, osteomyelitis, endocarditis and septicaemia in both humans and animals 10 , 18 , including within the bat colony at Jersey zoo 19 . S. aureus therefore provides an excellent model to examine the extent to which the resident, and potentially adaptive, microflora in captive animals might be perturbed due to antibiotic therapy, or else forced to compete against potentially pathogenic strains carried by co-residing species or their human contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike domestic animals, staphylococcal carriage is poorly documented in wildlife. Several Staphylococcus species were found in a captive population at Jersey Zoo (Jersey, Channel Islands, United Kingdom; Fountain et al, 2019 ). Bats were sampled by swabbing from ventral wing skin and oropharynx, as well as from mouth ejecta and skin lesions.…”
Section: Bacteriamentioning
confidence: 99%